Review of Teaching Methods and Critical Thinking Skills. - KOWALCZYK, NINA (Radiologic Technology)
Background Critical information is needed to inform radiation science educators regarding successful critical thinking educational strategies. From an evidence-based research perspective, systematic reviews are identified as the most current and highest level of evidence. Analysis at this high level is crucial in analyzing those teaching methods most appropriate to the development of critical thinking skills. Objectives To conduct a systematic literature review to identify teaching methods that demonstrate a positive effect on the development of students' critical thinking skills and to identify how these teaching strategies can best translate to radiologic science educational programs. Methods A comprehensive literature search was conducted resulting in an assessment of 59 full reports. Nineteen of the 59 reports met inclusion criteria and were reviewed based on the level of evidence presented. Inclusion criteria included studies conducted in the past 10 years on sample sizes of 20 or more individuals demonstrating use of specific teaching interventions for 5 to 36 months in postsecondary health-related educational programs. Results The majority of the research focused on problem-based learning (PBL) requiring standardized small-group activities. Six of the 19 studies focused on PBL and demonstrated significant differences in student critical thinking scores. Conclusion PBL, as described in the nursing literature, is an effective teaching method that should be used in radiation science education.